Elemen Keberagamaan Pada Tradisi Kompolan Shalawat Nariyah Dalam Membangun Solidaritas Sosial Masyarakat - Khairul Anwar; Moh. Nihwan (JSP: Jurnal Studi Pesantren, 2023)
This paper aims to explore the key dimensions of the Kompolan Shalawat Nariyah practice and its implications for the development of social solidarity among the Moncek Barat community. The study employs a qualitative research method to uncover the deeper meaning of this religious gathering, focusing on the symbolic and experiential aspects embedded in the tradition. The analysis is grounded in Emile Durkheim’s theory of religious sociology and the religious dimension theory proposed by C. Y. Glock and R. Stark. The research reveals that Kompolan Shalawat Nariyah is not merely a ritual of prayer recitation, but a dynamic social practice encompassing five main dimensions: belief, ritual, religious experience, knowledge, and consequences. These dimensions significantly influence the psychological well-being of its members, fostering inner peace, spiritual focus, and increased devotion. Socially, the group cultivates a sense of collective religious consciousness, where shared sentiments lead to strong group cohesion. This solidarity extends beyond spiritual aspects, manifesting in mutual support and even economic cooperation, highlighting the group’s role in strengthening communal bonds and resilience.